Analisis Learning Loss dan Strategi Pemulihan Pembelajaran di SDN Gerbo VI - Devinda Syaskia Maharani; Zafra Farah Statnia; Lika Hucha May Saroh; Dea Ayu Agistha; Salfa Vibrianti; Beti Istanti Suwandayani (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study aims to analyze the phenomenon of learning loss among students at SDN Gerbo VI and to examine the strategies implemented by teachers to restore basic learning skills after the period of online learning during the COVID-19 pandemic. The research employed a qualitative approach with a descriptive design. Data were collected through semi-structured interviews with teachers and the school principal, classroom observations during remedial learning sessions, and document analysis of teaching modules, assessment results, and student progress records. The findings indicate that learning loss remains evident in several areas, particularly decreased learning motivation, weakened focus and concentration, and declining basic literacy and numeracy skills. Increased dependence on gadgets following prolonged online learning has also negatively affected students’ attention span and study habits during face-to-face instruction. To address these challenges, teachers applied various recovery strategies, including active learning through group discussions, educational games, and the use of projector-based media, all of which helped enhance student engagement and classroom participation. However, recovery efforts are still constrained by limited parental involvement due to time constraints and low educational backgrounds, resulting in minimal learning support at home. Additionally, the surrounding social environment significantly influences students’ learning behavior and consistency. This study concludes that overcoming learning loss requires sustained collaboration among teachers, parents, and the community, as well as the implementation of adaptive and varied instructional strategies to ensure more effective and continuous improvement of students’ basic learning competencies.